Cnh1 Na(+) /H(+) antiporter and Ena1 Na(+) -ATPase play different roles in cation homeostasis and cell physiology of Candida glabrata - Krauke, Yannick; Sychrova, Hana (FEMS yeast research, 2011)
Yeasts tightly regulate their intracellular concentrations of alkali metal cations. In Saccharomyces cerevisiae, the Nha1 Na(+) /H(+) -antiporter and Ena1 Na(+) -ATPase, mediate the efflux of toxic sodium and surplus potassium. We report the characterization of Candida glabrata CgCnh1 and CgEna1 homologues. Their substrate specificity and transport properties were compared upon expression in S. cerevisiae, and their function characterized directly in C. glabrata. The CgCnh1 antiporter and the CgEna1 ATPase transport both potassium and sodium when expressed in S. cerevisiae. CgEna1p fully complements the lack of S. cerevisiae own Na(+) -ATPases but the activity of the CgCnh1 antiporter is lower than that of ScNha1p. Candida glabrata deletion mutants and analyses of their phenotypes revealed that though both transporters have a broad substrate specificity, their function in C. glabrata cells is not the same. Their differing physiological roles are also reflected in their regulation of expression, CgENA1 is highly upregulated by an increased osmotic pressure or sodium concentration, whereas CgCNH1 is expressed constitutively. The Cnh1 antiporter is involved in the regulation of potassium content and the Ena1 ATPase in sodium detoxification of C. glabrata cells. This situation differs from S. cerevisiae, where the Nha1 antiporter and Ena ATPases both participate together in Na(+) detoxification and in the regulation of K(+) homeostasis.
Keywords: Candida glabrata; kationty; Sodium; draslík; Genetic Complementation Test; Substrate Specificity; fungální proteiny; Potassium; Cations; delece genu; Gene Deletion; homeostáza; substrátová specifita; Homeostasis; sodík; Saccharomyces cerevisiae; Sodium-Hydrogen Exchangers; regulace genové exprese u hub; Gene Expression Regulation, Fungal; testy genetické komplementace; Fungal Proteins; Na(+)-H(+) antiport